Penggunaan Metode Problem Based Learning Untuk Meningkatkan Kemampuan Menulis Eksposisi dan Berpikir Kritis Siswa SMA - Nanang Maulana (Universitas Mathla'ul Anwar Banten, 2015)
This research is motivated by the lack of ability of the students in writing skills. Learning to write especially in school is less to get the dominant concern. So, students’ skills in writing are still very low. Psychologically most students assume that writing activities as a burden because they feel less able to use the Indonesian properly. Methodologically, the teacher are generally less variable in choosing the method use. Another reason underlying this study is students’ critical thinking is very low. This is due to lack of attention to critical thinking of studens in the school. Based on thrse reason, a method of problem based learning and tested in SMAN 19 Bandung should be applied. The purpose of this study id to determine the result of applying the method in teaching writing and critical thinking exposition. To achieve these objectives the method use in this study is quasi-experimental.